2001
DOI: 10.1037/1099-9809.7.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Racial identity and reflected appraisals as influences on Asian Americans' racial adjustment.

Abstract: J. E. Helms's (1990) racial identity psychodiagnostic model was used to examine the contribution of racial identity schemas and reflected appraisals to the development of healthy racial adjustment of Asian American university students (N = 188). Racial adjustment was operationally defined as collective self-esteem and awareness of anti-Asian racism. Multiple regression analyses suggested that racial identity schemas and reflected appraisals were significantly predictive of Asian Americans' racial adjustment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 9 publications
9
113
0
Order By: Relevance
“…He also suggested that methodological limitations of prior studies on mental health have led to underestimations of Asian Americans' rate of psychological disorders. The studies that have been conducted on psychological well-being of Asian Americans have shown relationships between racial identity, ethnic identity, and self-esteem (Alvarez, 2002;Alvarez & Helms, 2001;Chua & Fujino, 1999;Kohatsu, 1992;Yip, 2003). Depending on the saliency of ethnic identity or racial identity to the student, its effect on self-esteem will vary (Yip).…”
Section: Professional Significancementioning
confidence: 99%
See 4 more Smart Citations
“…He also suggested that methodological limitations of prior studies on mental health have led to underestimations of Asian Americans' rate of psychological disorders. The studies that have been conducted on psychological well-being of Asian Americans have shown relationships between racial identity, ethnic identity, and self-esteem (Alvarez, 2002;Alvarez & Helms, 2001;Chua & Fujino, 1999;Kohatsu, 1992;Yip, 2003). Depending on the saliency of ethnic identity or racial identity to the student, its effect on self-esteem will vary (Yip).…”
Section: Professional Significancementioning
confidence: 99%
“…Scales for measuring racial identity development have undergone various iterations ranging from the Racial Identity Attitude Scale, which primarily measured Black racial identity and was more closely linked to Cross' model of Nigrescence, to the Cultural Identity Attitudes Scale to the Visible Racial/Ethnic Identity Attitude Scale (VREIAS), which began to encompass other communities of color, to the more contemporary People of Color Racial Identity Attitude Scale (PRIAS) (Alvarez & Helms, 2001;Helms & Carter, 1990;Kohatsu, 1992;Liu, 2002;Parham & Helms, 1985;Pyant & Yanico, 1991;Solberg et al, 1994). Both the VREIAS and the PRIAS have been used as valid instruments to measure Asian American racial identity development and will be discussed further in the methodology section (Alvarez & Helms, 2001;Kohatsu, 1992;Liu, 2000Liu, , 2002.…”
Section: General Racial Identity Literaturementioning
confidence: 99%
See 3 more Smart Citations